Development of Matching Card Media as an Evaluation Tool on Mole Concept Subject - Erlina; Lestari, Ira; Jati, Prameswara Wahyu (Universitas Pendidikan Mandalika, 2025)
This study aims to measure the feasibility level and students' responses to the matching card media that was developed. This type of research is Research and Development with the 4D development model. Data collection techniques in this study used measurement techniques in the form of feasibility tests and student response questionnaires using a Likert scale. The subjects of this study were the matching card media, with trial subjects being XI MIPA 1 students at SMA Negeri 5 Pontianak. Feasibility testing used the Gregory test conducted by two media experts and two graphic design experts. The feasibility test on the developed media met very high criteria with an average score of 1.00 in the material aspect and 1.00 in the graphics aspect. Students' responses to the media in the limited and main field tests were 95.58% and 92.55%, respectively, with very good criteria. Based on the results obtained, it can be concluded that the matching card media as an evaluation tool for the mol concept material is very feasible and received a very positive response. This study contributes to the development of interactive evaluation media for the mole concept material, which can enhance students' understanding, engagement, andmotivation.